ANALISIS KLASTER INFRASTRUKTUR SEKTOR KESEHATAN DI WILAYAH KABUPATEN WONOGIRI TAHUN 2021 MENGGUNAKAN METODE ALGORITMA K-MEANS - Faradiba Santoso (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
Equalizing the development of health infrastructure is one way to improve the Human Development Index (HDI). A high HDI indicates the successful improvement of societal well-being in a region. This research discusses the utilization of the k-means algorithm to cluster sub-districts in Wonogiri Regency based on the similarity of health infrastructure using five metrics: the number of general hospitals, inpatient community health centers, outpatient community health centers, private clinics, and integrated health posts (posyandu). Three clusters were identified based on the distribution of health infrastructure: Cluster 1 consists of the following sub-districts: Paranggupito, Giritontro, Batuwarno, Karangtengah, Wuryantoro, Manyaran, Ngadirojo, Sidoharjo, Jatiroto, Bulukerto, Puhpelem, Slogohimo, Jatisrono, and Jatipurno. Cluster 2 consists of the following sub-districts: Giriwoyo, Tirtomoyo, Nguntoronadi, Eromoko, Kismantoro, Purwantoro, and Girimarto. Cluster 3 consists of the following sub-districts: Pracimantoro, Baturetno, Selogiri, and Wonogiri. By analyzing the distribution of health infrastructure, significant differences were observed among the clusters. In enhancing the HDI of Wonogiri Regency, the findings of this research can be utilized for government program planning to promote equitable development of health infrastructure.